The Impact of Sympathetic Magnetisation Transients on Harmonic Filters in Auto-Transformer Fed Railway Traction Applications - Wolfs, Peter (The University of Adelaide, 2009)
The operation of mixed fleets of modern PWM rectifier and older thyristor locomotives and the tightening of harmonic emission standards globally will lead to more complex harmonic filter installations in railway applications. This paper shows that track switching operations in an auto-transformer fed system can generate sympathetic transformer magnetization currents that have very significant magnitudes, high harmonic content and last for some seconds. A sympathetic transient can occur when un-energized auto-transformers are switched into service and paralleled with energized transformers at the feeder station or in adjacent track sections. The harmonic loads imposed by these currents need to be considered in the design of the harmonic filter elements and protection.